Delayed Fluorescence Emitter Enables Near 17% Efficiency Ternary Organic Solar Cells with Enhanced Storage Stability and Reduced Recombination Energy Loss. (20th February 2020) - Du, Xiaoyang; Yuan, Yi; Zhou, Lei; Lin, Hui; Zheng, Caijun; Luo, Junyi; Chen, Zhenhua; Tao, Silu; Liao, Liang‐Sheng
Abstract: Charge transfer state (CT) plays an important role in exciton diffusion, dissociation, and charge recombination mechanisms. Enhancing the utilization and suppressing the recombination process of CT excitons is a promising way to improve the performance of organic solar cells (OSCs). Here, an effective method is presented via introducing a delayed fluorescence (DF) emitter 3, 4‐bis(4‐(diphenylamino)phenyl)acenaphtho[1, 2‐ b ]pyrazine‐8, 9‐dicarbonitrile (APDC‐TPDA) in OSCs. The long‐lifetime singlet excitons on APDC‐TPDA can transfer to polymer donors to prolong exciton lifetime, which ensures sufficient time for diffusion and dissociation. Concurrently, the high triplet energy level (T1 ) of the DF material can also prevent the reverse energy transfer from CT to T1 . APDC‐TPDA‐containing ternary OSCs shows a high PCE of 16.96% with a reduced recombination energy loss of 0.46 eV. It is noteworthy that the ternary OSC also exhibits superior storage stability. After 55 days of storage, the PCE of the ternary OSC still retains about 96% of its primitive state. Furthermore, this ternary strategy is efficient and universally applicable to OSCs, and positive results can be obtained in different systems with different DF emitters. These results indicate that the ternary strategy provides a new design idea to realize high performance OSCs. Abstract : Herein, 17% efficient and stable ternary organic solar cells are realized by introducing a delayed fluorescence material 3, 4‐bis(4‐(diphenylamino)phenyl)acenaphtho[1, 2‐ b ]pyrazine‐8, 9‐dicarbonitrile (APDC‐TPDA) in a non‐fullerene system. Long‐lifetime singlet excitons on APDC‐TPDA can transfer to the polymer donor to prolong the excitons lifetime and suppress the reverse energy transfer from charge transfer state to triplet state, and then reduce the recombination energy loss of the device.